Revisiting Duhem: quasars, cosmology, and the tripartite relationship between theories and experiments. - Rodrigues, Danilo; Chiappin, Jose; Teixeira, Ramachrisna; Lucena da Silva, Jojomar (Cadernos de Astronomia, 2026)
This essay examines the work of the physicist and philosopher of science Pierre Duhem, whose contributions anticipated by more than fifty years several elements later developed in the epistemologies of Popper, Kuhn, and Lakatos. Duhem argued that scientific progress cannot be adequately described as a simple confrontation between theory and experiment. Instead, it involves a tripartite relationship in which competing theories are compared in light of experimental results, with experiments functioning mainly as a basis for comparison and theory choice. To illustrate Duhem’s theses, we discuss the early detections of quasars and their role in the cosmological debate between the Big Bang and the Steady State theories. The observed variation in the number of quasars over cosmic time indicated that the Universe is a dynamically evolving physical system, a feature predicted by the Big Bang theory but not explained within the Steady State model.
Keywords: Duhem; cosmology; quasars; theories